Anterograde Jelly belly ligand to Alk receptor signaling at developing synapses is regulated by Mind the gap. - Rohrbough, J.; Broadie, K. (Development, 2010)
Bidirectional trans-synaptic signals induce synaptogenesis and regulate subsequent synaptic maturation. Presynaptically secreted Mind the gap (Mtg) molds the synaptic cleft extracellular matrix, leading us to hypothesize that Mtg functions to generate the intercellular environment required for efficient signaling. We show in Drosophila that secreted Jelly belly (Jeb) and its receptor tyrosine kinase Anaplastic lymphoma kinase (Alk) are localized to developing synapses. Jeb localizes to punctate aggregates in central synaptic neuropil and neuromuscular junction (NMJ) presynaptic terminals. Secreted Jeb and Mtg accumulate and colocalize extracellularly in surrounding synaptic boutons. Alk concentrates in postsynaptic domains, consistent with an anterograde, trans-synaptic Jeb-Alk signaling pathway at developing synapses. Jeb synaptic expression is increased in Alk mutants, consistent with a requirement for Alk receptor function in Jeb uptake. In mtg null mutants, Alk NMJ synaptic levels are reduced and Jeb expression is dramatically increased. NMJ synapse morphology and molecular assembly appear largely normal in jeb and Alk mutants, but larvae exhibit greatly reduced movement, suggesting impaired functional synaptic development. jeb mutant movement is significantly rescued by neuronal Jeb expression. jeb and Alk mutants display normal NMJ postsynaptic responses, but a near loss of patterned, activity-dependent NMJ transmission driven by central excitatory output. We conclude that Jeb-Alk expression and anterograde trans-synaptic signaling are modulated by Mtg and play a key role in establishing functional synaptic connectivity in the developing motor circuit.